PERAN STRATEGIS SISTEM EKONOMI ALTERNATIF BAGI PEMBANGUNAN BANGSA DAN NEGARA - Musta'an Musta'an (ITB AAS INDONESIA, 2016)
The purpose of this study is to see how the strategic role of alternative economic system, in this case is the Islamic economic system for the development of the nation and state of Indonesia. The research method used is by using literacy study. The results obtained that the Islamic economic system as an alternative economic system has been proven with the advancement of sharia banks, although the development is slow, because constrained many things such as minimal capital, regulations that have not reached the real application, human resources, low understanding of the community, maximum, monetary tools used by the state still use interest, limited office network, and services that have not been able to meet the standards as do conventional banks. However, the Islamic economic system has helped in strengthening the economic development of the nation and the country especially when the crisis occurred in 1998 until today.